Rapid-Acting Antidepressants and Underlying Mechanisms - Samuel E Wilson; Meta Chen; Hiren Darji (Intelektual Pustaka Media Utama, 2016)
Loss of glial cells with resulting atrophy of the medial prefrontal cortex (mPFC) as well as the hippocampal area is demonstrated in depressed patients by brain imaging and postmortem studies. The mPFC is the master control of mood and emotional response. The hippocampus is part of the limbic system, the main function of which is to regulate emotions. The mPFC depends on the hippocampus for rapid learning and memory consolidation. Unlike monoamine reuptake inhibitor antidepressants, which take 6 to 8 weeks to exert their full effects, and with 30 - 40% unresponsive rate, ketamine acts rapidly, within a couple of hours, and has higher responsive rates. It suggests that in theory, due to its rapid effect, Ketamine could well serve as a bridging remedy to lower the rate of suicidal risk before Selective serotonin re-uptake inhibitors (SSRIs) reach their full effect for long-term depression management. Yet, ketamine has long been linked with abusive potential and possible neurotoxicity if used in large doses over a prolonged period. Even though there are no collected data to prove the associated adverse effects, awareness of this negative aspect of ketamine is sufficiently widespread to propel the psychiatric community to look for other rapidly acting antidepressant alternatives. Recent studies have shown that scopolamine, the Yueju pill, and magnesium are rapid-onset antidepressants that have mechanisms comparable to that of ketamine. These rapid-acting antidepressant agents promise to be effective and safer choices for depression management in the future, providing that further studies and investigations to produce a better and fuller understanding of their effects and limitations.